2021
DOI: 10.1080/14658011.2021.1993677
|View full text |Cite
|
Sign up to set email alerts
|

Properties of textile air conditioner waste dust-filled polyurethane rigid foam composites

Abstract: This paper investigates the morphology, mechanical and thermal insulation properties of textile air conditioner dust-filled polyurethane (PU) rigid foams. Textile air conditioner dust occurs during the spinning process of staple fibres. It consists of cotton fibre impurities as boll, leaf, and short fibres that generate a vast environmental load. This dust is used as a filler and dispersed in polyurethane up to 40% wt. The cell -size of foams decreased and cell -density increased by the increase in filler rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Thermal insulation properties deteriorated relative to plain PU. This study concluded that using air conditioning waste deteriorated the properties of polyurethane [4]. Similarly, Möhl et al studied composites made up of polylactic acid (PLA) and PLA Ingeo™ yarn as a matrix and reinforced it with cotton and flax fiber waste from the spinning industry.…”
Section: Composite Materialsmentioning
confidence: 95%
See 2 more Smart Citations
“…Thermal insulation properties deteriorated relative to plain PU. This study concluded that using air conditioning waste deteriorated the properties of polyurethane [4]. Similarly, Möhl et al studied composites made up of polylactic acid (PLA) and PLA Ingeo™ yarn as a matrix and reinforced it with cotton and flax fiber waste from the spinning industry.…”
Section: Composite Materialsmentioning
confidence: 95%
“…Özkan Buzğan et al prepared composites using air conditioner dust that consisted of short fibers, leaf particles, cotton boll pieces, etc. They faced the issues with control of material during composite fabrication [4]. Another study of dead waste was conducted by Barczewski et al in which they prepared composite from linseed cake (a byproduct from the linseed oil extraction process) but could not achieve good mechanical properties [86].…”
Section: Challenges Associated With Using Textile and Agriculture Was...mentioning
confidence: 99%
See 1 more Smart Citation